An economic impact analysis of mineral beneficiation in Kwazulu-Natal's iron and steel and aluminium value chain - Hearn, Nikol Anuschka (School of Economics, 2015)
This paper examines mineral beneficiation within the aluminium and iron & steel industries in Kwazulu-Natal and the associated value chains. Multiplier analysis is used in conjunction with the provincial social accounting matrix to determine the knock on effects of increased beneficiation, exploring the relevant impact of backward linkages. The multipliers created by both direct and indirect stimulation in the downstream industries are examined and the impacts of beneficiation on economic and welfare indicators are assessed. The key findings of the study are that the net effect on regional production is more than double the value of the initial stimulation for each of the considered sectors in the value chain. Moreover, job creation becomes evident when demand increases and that much of this employment go to the previously disadvantaged. There are however relevant drawbacks in terms of constrained electricity supply and significant leakages created by imports